1995
DOI: 10.1007/bf00116345
|View full text |Cite
|
Sign up to set email alerts
|

Joint action of combinations of pollutants on the acetylcholinesterase activity of several marine species

Abstract: : Acetylcholinesterase (AChE) is used as a specific biomarker of the effects of organophosphorous (OP) and carbamate (C) insecticides on the coastal marine environment. Studies of mixtures (by pairs) of five of these substances showed cumulative, synergistic inhibitory effects in all cases. The strongest synergy was observed in organophosphate-carbamate mixtures (OP-C) and the least in mixtures of substances of the same type (OP-OP, C-C). The intensity of the synergistic effect was directly related to the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
44
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 21 publications
7
44
1
Order By: Relevance
“…Carbofuran appeared to be the most efficient inhibitor (I 5o = 4.1 x 10 -7 M) compared to the other pesticides tested (I 50 > 4.1 x 10 -7 M). A similar result was reported by Bocquene et al (1995). Chlorfenvinphos and diazinon are moderate inhibitors, whereas chlor-pyrifos is a weak inhibitor This observation on chlorpyrifos is in agreement with the work of Bocquene et al (1995) and Olson and Christensen, (1980), who reported that many organophosphate pesticides are less efficient inhibitors before becoming metabolically transformed from thio to oxy analogs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Carbofuran appeared to be the most efficient inhibitor (I 5o = 4.1 x 10 -7 M) compared to the other pesticides tested (I 50 > 4.1 x 10 -7 M). A similar result was reported by Bocquene et al (1995). Chlorfenvinphos and diazinon are moderate inhibitors, whereas chlor-pyrifos is a weak inhibitor This observation on chlorpyrifos is in agreement with the work of Bocquene et al (1995) and Olson and Christensen, (1980), who reported that many organophosphate pesticides are less efficient inhibitors before becoming metabolically transformed from thio to oxy analogs.…”
Section: Discussionsupporting
confidence: 91%
“…A similar result was reported by Bocquene et al (1995). Chlorfenvinphos and diazinon are moderate inhibitors, whereas chlor-pyrifos is a weak inhibitor This observation on chlorpyrifos is in agreement with the work of Bocquene et al (1995) and Olson and Christensen, (1980), who reported that many organophosphate pesticides are less efficient inhibitors before becoming metabolically transformed from thio to oxy analogs. The abnormalities in fish behavior observed in this study could be related to failure of energy production or the release of stored metabolic energy, which may cause severe stress, leading to the death of the fish (Chakraborty et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These enzymes may be soluble, linked to the basal lamina via a collagen tail or to membrane via a glycolipid or via a hydrophobic peptide (Bon et al 1979;Massoulie and Bon 1982). The toxicity of OP and C insecticides toward AChE has been extensively studied both in insects and vertebrates (Bocquene et al 1995;Coppage and Mathews 1974;Haubruge and Toutant 1997;Sharma et al 1993). The accepted mode of action of these insecticides is to phosphorylate or carbamilate AChE enzyme (Fleming and Grue 1981).…”
mentioning
confidence: 99%
“…Moreover, some pesticides are used in fish farming. Those applications cause great damage to fish populations (Bocquene et al 1995). Acetylcholinesterase, the primary enzymatic target of OP and C is commonly used to detect their impacts (Bastos et al 1991;Fossi et al 1995;Westlake et al 1981a;Westlake et al 1981b).…”
mentioning
confidence: 99%